Comparative Analysis of AES-Turbo Code Combination Encryption Method on Three Variations AES Key - rendra bayu adi (International Journal of Science, Engineering, and Information Technology, 2017)
Data communication is a process of sending information from two or more points using a binary code. In data communication sometimes it does not run smoothly, while the obstacle in the process of sending information is data theft until data damage Information is exposed to noise in the process. Therefore we need an application that can provide information security and at the same time avoid damage to data due to noise. One such application is to combine AES cryptographic techniques with forward techniques error correction in the form of Turbo code. This study aims to combine the two techniques and apply to text data and analyze based on the length of the encryption key owned by AES. The analysis shows that the AES-turbo cryptographic combination algorithm can work optimally with the percentage of data returned 100% at the SNR of 15 dB. In testing the avalance effect also shows that a 256-bit key length is safer, this is evidenced by the Avalanche Effect trial of 24.77362%. But in testing the data execution time, the longer the key the longer it takes for encryption and decryption. Thus for the selection of 3 key variations of AES that are more efficient and effective, that is by using a 128-bit key.